PHYSICAL EDUCATION OF STUDENTS INCREASING PHYSICAL TRAINING WITH MEANS (Academicia Globe: Inderscience Research, 2021)
The article deals with the issues of preparing future students of physical education for innovative activities, the organization of the content of physical education lessons on a scientific basis, modernization of its organizational and technological bases, development of future development trends. And its outcome is in the public interest, to guide young people towards social relations, to realize the natural potential of man to gain social experience.